The interaction of oral and written traditions in the works of Âşık Maksut Feryadî - Erdem, E. Nisan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
In this thesis, what it means to be a minstrel in the contemporary literary environment in Turkey is examined, and for this, the poems of Maksut Koca (Feryadî), his performance- based literary activity and strategies to make himself visible in the public socio-economically are used as examples. In the first part of the study, the electronic medium, which has become increasingly widespread today and is important for positioning the minstrel literature in the cultural production of the modern age, has been examined in detail within the framework of Walter Ong's concept of secondary orality. In the second part, the relationship between Maksut Koca's works and his life with oral, written and contemporary electronic media is studied. In the third chapter, it has been taken into account that there is not only a linear relationship between the work, the author and the reader, but also a capital relationship, and that there are intermediaries in the process of the creation and printing of the work. For this reason, today's minstrel literature is viewed as a "literary event" in which books and secondary orality play a role in its circulation. In this part, which is shaped as a study of literary sociology, minstrel books, publishing houses and Maksut Koca's printed work Sular Yandı are examined. At the end of the study, the written text of two interviews with Maksut Koca is added.
Keywords: Koca, Maksut, 1961- -- Criticism and interpretation.; Folk poetry, Turkish.; Folk literature, Turkish.